2022
DOI: 10.1039/d1nj05919j
|View full text |Cite
|
Sign up to set email alerts
|

A pyridine based Schiff base as a selective and sensitive fluorescent probe for cadmium ions with “turn-on” fluorescence responses

Abstract: A new fluorescent probe based on pyridine Schiff base (2-(pyridine-2-ylmethylene)phenoxyaniline, PMPA) working with PET mechanism and chelation enhanced fluorescence (CHEF) was designed and synthesized for the selective detection of cadmium...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The sensor has a binding constant of 4.36 × 10 4 M −1 and a detection limit of 5.74 × 10 −7 M. It has been successfully utilized for accurate detection in tap water samples. PMPA was designed and synthesized as a probe customized by pyridine derivatives with the photoinduced electron transfer (PET) mechanism and chelation-enhanced fluorescence (CHEF) properties for the selective detection of Cd 2+ in ACN [78]. The probe exhibits a wide pH range flexibility (5-9), quick response time (3 min), excellent sensitivity (LOD = 0.12 mM), and favorable reversibility.…”
Section: Fluorescent Probes To Detect CD 3+mentioning
confidence: 99%
See 1 more Smart Citation
“…The sensor has a binding constant of 4.36 × 10 4 M −1 and a detection limit of 5.74 × 10 −7 M. It has been successfully utilized for accurate detection in tap water samples. PMPA was designed and synthesized as a probe customized by pyridine derivatives with the photoinduced electron transfer (PET) mechanism and chelation-enhanced fluorescence (CHEF) properties for the selective detection of Cd 2+ in ACN [78]. The probe exhibits a wide pH range flexibility (5-9), quick response time (3 min), excellent sensitivity (LOD = 0.12 mM), and favorable reversibility.…”
Section: Fluorescent Probes To Detect CD 3+mentioning
confidence: 99%
“…Furthermore, it has been successfully applied to determine real water samples. in ACN [78]. The probe exhibits a wide pH range flexibility (5-9), quick response time (3 min), excellent sensitivity (LOD = 0.12 mM), and favorable reversibility.…”
Section: Fluorescent Probes To Detect CD 3+mentioning
confidence: 99%
“…With a detection limit of 1.025 × 10 −8 M, a Rhodamine-based Schiff-base fluorescence chemosensor 9 was used to find Cd 2+ ions. In the presence of cations, the chemosensor 9 shows significant sensitivity and selectivity for Cd 2+ ions [44]. An ON-type Schiff base chemosensor 10 was communicated in 2020 and its fluorescence properties against cadmium ions were discussed.…”
Section: Detection Of Cadmium Ionmentioning
confidence: 99%
“…47 Sooksimuang et al in 2022 reported a tetrahydro- [5]helicene based uorescent sensor, which detects Cd 2+ in H 2 O/dioxane (1/19, v/v), 48 while Dong's group in 2022 reported a pyridine based Schiff base for detection of cadmium ions with a 'turn-on' uorescence response and a LOD value of 0.12 mM in acetonitrile. 49 A phenazine-imidazole based ratiometric uorescent probe was designed by Wang et al to recognise Cd 2+ ions only in 2022, which showed a limit of detection value of 2.10 × 10 −8 (M). 50 Although Schiff bases containing N, O, S donors binding with Cd 2+ with 2 : 1 stoichiometry are less known, Rajesh et al in 2021 published a work on a quinoline based Schiff base for detecting cadmium in semi aqueous medium with 2 : 1 stoichiometry and a LOD value of 14.8 nM.…”
Section: Introductionmentioning
confidence: 99%